Réponses

2012-09-23T10:07:40+02:00

E=8-(-3+(5-4x3)

=8-(-3+(5-12)

=8-(-3-7)

8-(-10)=8+10=18

 

 

F=- 5 x (-3+2) - (-8+2) x (-1) 

=-5x(-1)-(-6)x(-1)

=-5x6=-30


H=-1x(2x(-3+4x(-5)+6-7)+8


=-1x(2x1x(-5-1)+8

=-1x2x(-6)+8

=-1x(-12)+8

=-12+8=-4


Voila je croi que c'est ca le G jai pas reussi :/ desoo

2012-09-23T10:18:19+02:00

E = 8-(-3+(5-4*3)) = 8-(-3+(5-12)) = 8-(-3-7) = 8+10 = 18

F= 5*(-3+2)-(-8+2)*(-1) =5*(-1)-(-6)*(-1)= -5-6 = -11

G = -10*(-7+2*(-4)) / -3 +7*2 = -10* (-7 -8) /-3+14 = 150 / 11

H = -1*(2*(-3+4*(-5)+6)-7)+8 = -1*(2*(-3 -20 +6)-7)+8 = -1*(2 *(-17)-7)+8 

H = -1*(-34-7+8 ) = -1*(-41+8) = -1*( -33) = 33